2009
DOI: 10.1007/s10973-009-0420-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the bond-strength-coordination number fluctuation model and the random walk model of viscosity

Abstract: We have studied the temperature dependence of the viscosity of some polymeric materials by using both, the bond strength-coordination number fluctuation model and the random walk model. The results reveal that both models show an excellent agreement with the experimental data. For the random walk model, two equations corresponding to two temperature regimes (low-T and high-T) separated by the critical temperature c T , which is difficult to determine, are needed to describe the temperature dependence of the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Furthermore, we have compared and discussed the interrelation between the VFT equation and the BSCNF model [25,26]. It has been found that in the case of γ = 1, the viscosity behavior described by Equation 1 with the set of parameters ( B , C ) obeying the relation Equation 3, perfectly follows the behavior described by the VFT equation, logη=AVFT+BVFTTT0, where A VFT is the logarithm of the viscosity at the high temperature limit, A VFT = log η 0 , and B VFT , T 0 are the free fitting parameters of the VFT equation.…”
Section: The Bscnf Model and The Vft Equationmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, we have compared and discussed the interrelation between the VFT equation and the BSCNF model [25,26]. It has been found that in the case of γ = 1, the viscosity behavior described by Equation 1 with the set of parameters ( B , C ) obeying the relation Equation 3, perfectly follows the behavior described by the VFT equation, logη=AVFT+BVFTTT0, where A VFT is the logarithm of the viscosity at the high temperature limit, A VFT = log η 0 , and B VFT , T 0 are the free fitting parameters of the VFT equation.…”
Section: The Bscnf Model and The Vft Equationmentioning
confidence: 99%
“…From the BSCNF model of the viscosity given in Equation 1, we obtain the fragility index m [23,24,25,26]. m=1ln(10){BC+2[ln(ηTgη0)+12ln(1B)]1B}.…”
Section: The Bscnf Model and The Vft Equationmentioning
confidence: 99%
See 3 more Smart Citations